Changes of chemical components of Tibetan tea during pile fermentation process - DENG Junlin; HE Yanghang; CHEN Jian; LIU Gang; XIA Chen (Shipin yu jixie)
Objective: The changes in the main chemical components in water extracts of Tibetan tea during the pile fermentation process were investigated. Methods: Research was done on tea samples and water extracts from various fermentation stages of Tibetan tea. Soluble solids, soluble sugars, total polyphenols, total flavonoids, and in vitro antioxidant activity (ABTS and DPPH) were all examined. Additionally, ultra-performance liquid chromatography (UPLC) was used to find theophylline, caffeine, gallic acid (GA), and 8 catechins monomers. By using enzyme-linked immunoassay, the amount of theaflavin, thearubigin, and theabrownin were determined. Results: The soluble solids in Tibetan tea reduced and then slightly increased during the fermentation process. The amount of soluble sugar, total polyphenols, and total flavonoids and the antioxidant activity decreased gradually. Caffeine showed a fluctuating state with small changes, the amount of GA and catechin (C) increased and then slightly decreased. Epicatechin (EC) and (gallocatechin gallate) GCG concentration increased and then decreased. Gallocatechin (GC), epigallocatechin (EGC), epicatechin gallate (ECG), and epigallocatechin gallate (EGCG) levels all showed a consistent reduction. The EGCG decreased from 39.69 mg/g in the initial tea to 1.36 mg/g in final product. The amount of theaflavin first climbed and then slightly dropped, the amount of thearubigin changed slightly, and the amount of theabrownin progressively increased (3.12 g/100 g in the original tea, 7.46 g/100 g in the completed tea). Conclusion: The changes in main chemical components during the fermentation process of Tibetan tea were revealed. These results might serve as guidelines for processing and quality control of Tibetan tea.